(3y+8)(1-y)=0

Simple and best practice solution for (3y+8)(1-y)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3y+8)(1-y)=0 equation:



(3y+8)(1-y)=0
We add all the numbers together, and all the variables
(3y+8)(-1y+1)=0
We multiply parentheses ..
(-3y^2+3y-8y+8)=0
We get rid of parentheses
-3y^2+3y-8y+8=0
We add all the numbers together, and all the variables
-3y^2-5y+8=0
a = -3; b = -5; c = +8;
Δ = b2-4ac
Δ = -52-4·(-3)·8
Δ = 121
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{121}=11$
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-5)-11}{2*-3}=\frac{-6}{-6} =1 $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-5)+11}{2*-3}=\frac{16}{-6} =-2+2/3 $

See similar equations:

| 2)5.6x+1.8-6.6=18.72 | | -9x35=10 | | -45+15=-5x+11x | | 6x+4.4x=5.2 | | −2x^2+9x−3=0 | | -3n-5=-48-40n | | 0=16x^2-167x+385 | | 7/x=4/74/100 | | -3n-5=-48+-40n | | 2x+20+4+40+6x+60=180 | | 10x+15+(5x)=180 | | 6x+34=8x+18 | | 1/8y+4=-11 | | 10x+12)+(5x)=180 | | (10x+12)(5x)=180 | | 6(b-3)=4b-4 | | 1/7y+4=-18 | | 60^3-120x=0 | | 3(n+2)+n=8n-8+6 | | -5+7+2k-3k=-8 | | 6v−5v=5 | | 2^y=5^y-2 | | 4(4x+2)-5=115 | | x/2=25-6 | | X-7=2/5x+20 | | -65+15=-2x+12x | | x÷2+4=8 | | 3y²-17y+6=0 | | 3/2t=1/3 | | 1.8x=1.6x+12.48 | | 4(x-2)+x=10 | | 8w-25w-40=13+5w |

Equations solver categories